2008
DOI: 10.1002/syn.20595
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2High receptors measured ex vivo are elevated in amphetamine‐sensitized animals

Abstract: Although dopamine supersensitivity is a fundamental aspect of diseases such as schizophrenia and Parkinson's disease, the molecular basis of dopamine supersensitivity is not known. Because behavioral dopamine supersensitivity is associated with a marked elevation of striatal dopamine D2High receptors in vitro, it is important to develop methods to measure D2High receptors in vivo. The present ex vivo study found that the dopamine agonist NPA ([-]-N-propyl-norapomorphine) inhibited the binding of the agonist Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Importantly, however, increases in the sensitivity of rats to the inhibitory effects of pramipexole on yawning corresponded to a significant decrease in k d for [ 3H ]-spiperone at D2-like receptors at 42d, suggesting that the observed behavioral changes were mediated by an increased affinity of pramipexole at the D 2 receptor. Although the current studies were not designed to differentiate between the high- and low-affinity states of D 2 receptors, it is possible that the increased sensitivity of the cocaine-treated rats to the D 2 -mediated inhibition of pramipexole-induced yawning was also influenced by an increased proportion of D 2 receptors in the high-affinity state as has been reported in rats following cocaine self-administration (Briand et al 2008), or sensitization to caffeine (Simola et al 2008), or amphetamine (Seeman 2009). In addition to providing convergent evidence to support a cocaine-induced sensitization of the D 2 receptor, the current studies also suggest that increases in D 3 receptor binding may underlie the progressive increase in the sensitivity of cocaine-treated rats to the D 3 -mediated induction of yawning by low doses of pramipexole.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, increases in the sensitivity of rats to the inhibitory effects of pramipexole on yawning corresponded to a significant decrease in k d for [ 3H ]-spiperone at D2-like receptors at 42d, suggesting that the observed behavioral changes were mediated by an increased affinity of pramipexole at the D 2 receptor. Although the current studies were not designed to differentiate between the high- and low-affinity states of D 2 receptors, it is possible that the increased sensitivity of the cocaine-treated rats to the D 2 -mediated inhibition of pramipexole-induced yawning was also influenced by an increased proportion of D 2 receptors in the high-affinity state as has been reported in rats following cocaine self-administration (Briand et al 2008), or sensitization to caffeine (Simola et al 2008), or amphetamine (Seeman 2009). In addition to providing convergent evidence to support a cocaine-induced sensitization of the D 2 receptor, the current studies also suggest that increases in D 3 receptor binding may underlie the progressive increase in the sensitivity of cocaine-treated rats to the D 3 -mediated induction of yawning by low doses of pramipexole.…”
Section: Discussionmentioning
confidence: 99%
“…No previous in vitro postmortem or in vivo imaging studies have investigated and reported on the availability of the physiologically more relevant D 2/3 agonist binding (as D 2/3 HIGH , and not D 2 LOW are the sites accessed by dopamine) in cocaine dependent humans. We were interested in this particular issue for two reasons (1) it was critical to understand whether the blunted displacement of [ 11 C]raclopride after amphetamine in cocaine dependence can be attributed to post-synaptic factors, i.e., a lower fraction of D 2/3 receptors configured in a state of high affinity for the agonists and (2) previous reports in rodents suggest that chronic exposure to psychostimulant drugs such as cocaine and amphetamine lead to a higher (~ 150%), not lower fraction of D 2/3 HIGH receptors (Briand et al, 2008; Seeman, 2009; Seeman et al, 2007; Seeman et al, 2002), which was contradictory to our predicted hypothesis. Thus, in this human imaging study, we investigated both the D 2/3 antagonist and D 2/3 agonist binding potential in a group of subjects who regularly abused cocaine for nearly two decades and found neither an increase nor a decrease in the available % R HIGH relative to healthy comparison subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, substances like amphetamine, phencyclidine, steroids, and ethanol, as well as some brain lesions have also been found to produce psychosis and dopamine super-sensitivity in humans. In this respect, it is of special interest that dopamine super-sensitivity can also be induced in rats and that this goes along with a two-to fourfold increase in the proportion of D 2 High receptors in their striatal membranes Seeman 2009Seeman , 2011. On the other hand, the total D 2 receptor concentration seems to be much less affected both in manipulated rodents and in schizophrenic patients (Farde et al 1990;Seeman et al 2002).…”
Section: Alterations In the Dmentioning
confidence: 95%